Bamboo forest therapy contributes to the regulation of psychological responses. Issue 1 (2nd January 2019) - Lyu, Bingyang; Zeng, Chengcheng; Deng, Songyuan; Liu, Shiliang; Jiang, Mingyan; Li, Nian; Wei, Lanqing; Yu, Yan; Chen, Qibing
ABSTRACT: Bamboo is widespread throughout southwestern China. Empirical field research on the health benefits of bamboo forest therapy is currently lacking. The objective of this research was to investigate the effects of a 3-day stay in a bamboo forest on the psychological responses of participants. In our study, 120 volunteers between the ages of 19 and 24, including 60 males and 60 females, participated in the test. Four sites were selected for the test, including two natural bamboo forests (YA and YB), a bamboo park (DJY), and an urban environment (CS). During the testing period, all participants were asked to view the landscape for 15 min in the morning and then walk in the testing area for 15 min in the afternoon. A profile of mood state questionnaire was used to evaluate mood. In the bamboo forest environment, the scores of the participants for tension and anxiety, anger and hostility, depression, fatigue, and confusion after forest therapy were significantly lower than those of the participants in the urban area, while the scores of these participants for vigor were significantly higher than those of the participants in the urban area. These findings provide scientific evidence that a 3-day session in a bamboo forest can increase positive mood and decrease negative mood. The potential for a longer-term effect on visitor psychological health requires further investigation.